3D motion dynamics of axisymmetric bodies falling through water. (1st December 2018) - Alsos, Hagbart S.; Faltinsen, Odd M.
Abstract: A new simplified method for analysis of 3D motion dynamics of axisymmetric slender bodies falling from air through water is presented. Slender-body theory for potential flow of incompressible water is combined with 2D  +  t theory to account for viscous cross-flow separation in the submerged phase. The effect of flow separation from the upstream end of a pipe plays an important role. Furthermore, asymmetric vortex shedding triggering important 3D motions is considered. The water impact loads are based on strip theory and empirical slamming coefficients together with added mass and buoyancy loads. The theory is validated by comparing numerical analyses with experimental drop tests of pipes performed by Aanesland (1987). Error analyses of the theoretical method are performed and compared with tests to explore the sensitivity to input variations.